Short term impact of artisanal dredges in a Patagonian mussel fishery: Comparisons with commercial diving and control sites - Narvarte, Maite Andrea (2012)
Mussels in the San Matías Gulf fishery are targeted using artisanal dredges and diving. The main objective of this study was to assess the direct impact of artisanal dredging on the biota and sediments, and to compare the composition of the catches and the individual damage induced by fishing between dredging and commercial diving. The experimental design included samplings from dredge catches, dredge tracks, control sites and commercial diving. According to their damage level, individuals were scored as undamaged, lightly damaged and severely damaged. Sediment characteristics were analyzed using coring samples and traps. Damage of mussels, mostly corresponding to the severely damaged category, was less than 5% both in samples from dredging and diving. Conversely, mean damage of the main bycatch species (sea urchins and ophiuroids) was 75 and 65% in samples from dredging and diving respectively, being most of the individuals lightly damaged. Considering also the catch sample composition of both fishing methods, dredging affected relatively more individuals than diving. Although sediment removal in dredged areas was three times higher than that in non-dredged ones, mean grain size and gravel percentage of sea floor sediments showed subtle differences between them.